A catarse na didática da pedagogia histórico-crítica - Duarte, Newton (UNICAMP - Faculdade de Educação, 2019)
Abstract Analyzing the didactic method of historical-critical pedagogy, the Brazilian educator Dermeval Saviani, defines catharsis as the culmination of the educative process. This paper explores the importance of catharsis to Didactics in that pedagogical perspective, taking the studies of György Lukács (1885-1971) and Antônio Gramsci (1891-1937) in that category as theoretical references. Catharsis is understood here as a qualitative leap in the process of expansion and enrichment of relations between individual subjectivity and social-cultural objectivity. It is, at the same time, an intellectual, emotional, educational, political and ethical transformation, that changes the worldview of the individuals and their relations with their own life, society and humankind.

Resumen Analizando el método didáctico de la pedagogía histórico-crítica, el educador brasileño Dermeval Saviani define la catarsis como la culminación del proceso educativo. Este artículo explora la importancia de la catarsis para la Didáctica en esa perspectiva pedagógica tomando como referencias teóricas los estudios de György Lukács (1885-1971) y Antônio Gramsci (1891-1937) sobre esta categoría. La catarsis se entiende aquí como un salto cualitativo en el proceso de ampliación y enriquecimiento de las relaciones entre la subjetividad individual y la objetividad sociocultural. Es, al mismo tiempo, una transformación intelectual, emocional, educativa, política y ética, que cambia la visión del mundo de los individuos y sus relaciones con su propia vida, la sociedad y la humanidad.

Resumo Segundo Dermeval Saviani, no método didático da pedagogia histórico-crítica, a catarse é o momento culminante. Este artigo explora a importância dessa categoria para a didática nessa perspectiva pedagógica, tomando como referências os estudos de György Lukács (1885-1971) e Antônio Gramsci (1891-1937) sobre o processo catártico. É defendida a interpretação de que a catarse seria um salto qualitativo no processo de ampliação e enriquecimento das relações entre a subjetividade individual e a objetividade sociocultural. Trata-se de uma transformação, ao mesmo tempo, intelectual, emocional, educacional, política e ética, que modifica a visão de mundo do indivíduo e suas relações com sua própria vida, com a sociedade e com o gênero humano.
Catharsis as a category in didactics from the perspective of historicalcritical pedagogy
Catarsis como una categoría didáctica en la perspectiva de la pedagogía histórico-crítica
Keywords: catharsis; didactics; historical-critical pedagogy; György Lukács; Antonio Gramsci; catarse; pedagogia histórico-crítica; didática; György Lukács; Antonio Gramsci